Policy-based Wide Area Network Management System - Odagiri, Kazuya; Shimizu, Shogo; Ishii, Naohiro (Discoveries in Agriculture and Food Sciences, 2014)
In the current Internet-based systems, there are many problems using anonymity of the network communication such as personal information leak and crimes using the Internet systems. This is because the TCP/IP protocol used in Internet systems does not have the user identification information on the communication data, and it is difficult to supervise the user performing the above acts immediately. As a solution for solving the above problem, there is the approach of Policy-based Network Management (PBNM). This is the scheme for managing a whole Local Area Network (LAN) through communication control of every user. In this PBNM, two types of schemes exist. The first is the scheme for managing the whole LAN by locating the communication control mechanisms on the course between network servers and clients. The second is the scheme of managing the whole LAN by locating the communication control mechanisms on clients. As the second scheme, we have been studied theoretically about the Destination Addressing Control System (DACS) Scheme. By applying this DACS Scheme to Internet system management, we realize the policy-based Internet system management. In this paper, we show the DACS system theoretically.